In vitro & in nivo anti-adipogenic effects of a standardized quassinoid composition from Eurycoma longifolia / Dharvind Balan - Dharvind, Balan (2019)
Dysregulation of adipocyte metabolism often leads to metabolic dysfunction and obesity. Comorbidities of obesity up-surge the medical risk factors in modern days society. Eurycoma longifolia Jack (EL) is an herbal medicinal plant native to South-East Asian countries, widely known as ‘Tongkat Ali.’ Bioactive compounds of EL were previously shown to reduce omentum fat mass and oestradiol-induced fatty uterine adhesion in rats. However, the exact role of EL in the modulation of adipogenesis remains to be investigated further. Therefore, this study sought to investigate the effects of a standardized quassinoids composition of EL (SQEL) on the adipogenesis of 3T3-L1 preadipocyte cells and in high-fat-diet-induced obese C57BL/6J mice. The 3T3-L1 cells were induced to differentiate and treated with various concentrations of SQEL (0-100 μg/mL) for 8 days. Oil Red O staining and intracellular triglyceride quantification assay were performed to determine the effect of SQEL on adipogenic differentiation and cytosolic triglyceride accumulation in 3T3-L1 cells. In addition, the effect of SQEL on lipolysis was also examined by quantifying glycerol released by mature adipocytes treated with SQEL at various concentrations. The mRNA and protein expressions of adipogenic markers were measured using qRT-PCR and immunoblot analysis, respectively. Similarly, C57BL/6J mice were fed with normal and high-fat diet and given 5 mg/kg and 10 mg/kg (i.p) of SQEL for 12 weeks. Weekly food intake and body weight were measured throughout the treatment period. Oral glucose tolerance and intraperitoneal insulin tolerance tests were conducted on the 12th week of the study. At the end of treatment, blood serum was collected for measurement of serum lipids. Epididymal and perirenal fat pads and liver were excised, weighed and used for iv histological studies. SQEL significantly inhibited adipogenesis and reduced intracellular accumulation of lipids in adipocytes. Moreover, the mRNA expression of major adipogenic transcription factors (PPARγ and C/EBPα) and markers (FAS, LPL and KLF15) were reduced while Sirt1 and FoxO3 proteins were upregulated during the initial stage of differentiation. On the other hand, SQEL also increased lipolysis by elevating glycerol production and reducing intracellular triglycerides in mature adipocytes. In addition, SQEL suppressed body weight gain and decreased epididymal and perirenal fat pad mass in both the normal and high-fat diet fed mice. Moreover, accumulation of fat in the liver and size of adipose tissue were found reduced with SQEL treatment in high-fat diet mice. SQEL treatment also induced energy expenditure in adipose tissue of mice on HFD by elevating the expression of thermogenic genes, AMPK and PGC-1α. Furthermore, SQEL also improved glucose intolerance and decreased elevated total cholesterol and triglyceride in mice fed with high-fat diet. These novel findings suggest that SQEL has an anti-adipogenic effect and could be explored as an alternative pharmacologic agent inhibiting cellular differentiation of pre-adipocytes for the prevention of obesity.